Educational Experiences Integrating Arts and Digital Technologies into the Curriculum - Escala, Nella (2024)
Integrating the arts in primary education has proven to be an effective strategy to enrich learning and foster greater student engagement in their educational process. In Ecuador, learning through the arts and the support of digital technologies remains an underexplored practice, especially in the disadvantaged socioeconomic contexts that characterize much of the country. A study was conducted to explore educational experiences integrating the arts and understand these interventions' didactic processes. Using an exploratory-descriptive ethnographic qualitative approach, data were collected through document analysis and interviews with actors from government agencies, international cooperation organizations, and cultural and educational institutions. The findings highlighted that collaboration between teachers and art specialists enables the design of deeper, more meaningful educational experiences while using digital technologies broadens student access and participation in these activities. Additionally, the sustainability of these initiatives largely depends on continuous, collaborative support between educational and cultural institutions.